Il Repertorio Nazionale dei Dati Territoriali nel contesto delle politiche di valorizzazione del patrimonio informativo pubblico - Ciasullo, Gabriele; Rotundo, Antonio (GEOmedia, 2014)
In the general framework defined by the policies on the enhancement of PSI, the National Catalogue for the Spatial Data represents an important reference element for the use of geographic information from the Italian users community. The activities developed in the first two years of operational phase go in the direction of making the Catalogue an essential tool in the "toolbox” of every geomaticians and, in perspective, of every citizen.